2020
DOI: 10.3390/su12051949
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Cranial Deformity and Delayed Development in Children

Abstract: Plagiocephaly, the most common form of cranial deformity, has become more prevalent in recent years. Many authors have described a number of sequelae of poorly defined etiologies, although several gaps exist in their real scope. This study aimed to analyze the effects of physiotherapy treatments and cranial orthoses on the psychomotor development of infants with cranial deformities, complemented by protocolized postural exercises applied by the family. This prospective study on different developmental areas in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Secondly, it is likely that the medical complications of brachycephaly were not serious enough to endure the discomfort and annoyance of the treatment. Deformational plagiocephaly is considered to be a risk for developmental delays [32,33]; however, the harmful effects of brachycephaly are controversial [8,9]. Recently, deformational plagiocephaly has been regarded as a consequence of early developmental delays, rather than the cause of delayed development [8,34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, it is likely that the medical complications of brachycephaly were not serious enough to endure the discomfort and annoyance of the treatment. Deformational plagiocephaly is considered to be a risk for developmental delays [32,33]; however, the harmful effects of brachycephaly are controversial [8,9]. Recently, deformational plagiocephaly has been regarded as a consequence of early developmental delays, rather than the cause of delayed development [8,34].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has also shown that brachycephaly is associated with lower cognitive and academic measures in adolescence [7]. The delays were explained with various mechanisms and these associations remain controversial [8][9][10][11]. Collett et al mentioned the mechanical mechanism in which a cranial deformity leads to the dysmorphology of brain [10], but some have described brain dysmorphology in infants with cranial deformity not being clearly associated with skull shape [8,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak can be observed at four months, and percentages are low after 8 months. Many cases of PP improve over time, but scientific evidence suggests that conservative management strategies can safely and effectively minimize the degree of cranial asymmetry [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The literature reports long-term clinical repercussions arising from the most severe cranial deformities, though unrelated to brain functions, such as deformities affecting orthodontic health and temporomandibular joint syndrome [5]. Several studies have reported an association between the presence of plagiocephaly and the delays in cognitive, language and motor development, which can persist up to 36 months of age [6][7][8][9]. Their results emphasize two hypothesized and potentially interacting pathways: environmental positioning as the primary driver for motor delays and simultaneously for plagiocephaly or an underlying central nervous system dysfunction as a primary driver of motor and cognitive delays, with motor delays leading to limited mobility and plagiocephaly [6][7][8].…”
Section: Introductionmentioning
confidence: 99%